1998
DOI: 10.1111/j.1439-0523.1998.tb01927.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of synthetic maize populations for resistance to Striga hermonthica

Abstract: can also be described as tolerance, in that high grain yields are The parasitic witchweed, Striga hermonthica (Del.) Benth, is the greatest attained in the presence of reduced host plant damage by Striga

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…It is interesting to note that even though the Striga-susceptible cultivar G6 had the lowest grain yield and the most severe Striga damage, the number of emerged Striga plants was lower or comparable with those of the Striga-tolerant cultivars such as G3, G4, G7 and G8. This confirms the reports of earlier workers, that Striga emergence count alone is not reliable for the evaluation of resistance, especially when cultivars are highly susceptible, because such materials suffer more damage, even when few Striga plants are attached to the roots of the host plant (Kim et al 1998). Therefore, for maximum gain from selection for Striga resistance and increased grain yield, it will be desirable to use a combination of grain yield, host damage syndrome rating and Striga emergence counts to improve both traits simultaneously.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is interesting to note that even though the Striga-susceptible cultivar G6 had the lowest grain yield and the most severe Striga damage, the number of emerged Striga plants was lower or comparable with those of the Striga-tolerant cultivars such as G3, G4, G7 and G8. This confirms the reports of earlier workers, that Striga emergence count alone is not reliable for the evaluation of resistance, especially when cultivars are highly susceptible, because such materials suffer more damage, even when few Striga plants are attached to the roots of the host plant (Kim et al 1998). Therefore, for maximum gain from selection for Striga resistance and increased grain yield, it will be desirable to use a combination of grain yield, host damage syndrome rating and Striga emergence counts to improve both traits simultaneously.…”
Section: Discussionsupporting
confidence: 92%
“…Striga hermonthica infestation is extremely difficult to control and is a major threat to the rapid spread of maize into the WCA savanna. Available Striga control measures include host plant resistance, cultural, chemical, and manual methods (Odhiambo and Ransom 1994;Kim et al 1998). Of these, the use of host plant resistance or tolerance is considered the most economical and environmentally friendly for resource-poor farmers.…”
mentioning
confidence: 99%
“…The same observation was made on the resistance mechanism of some cereal cultivars in Striga controlling (Kuiper et al, 1998). The existence of differences in cultivar susceptibility against Striga hermonthica has been highlighted among sorghum cultivars (Omanya et al, 2004;Rodenburg et al, 2006) and maize (Zea mays L.) cultivars (Kim et al, 1998). Our results confirmed that of Hariri (1990) and Dibong et al (2009) from their experiments on artificial infestations with other species of Loranthaceae.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, screening for host plant resistance under very high infestation levels, using number of aboveground Striga plants as screening measure, might result in underestimation of susceptibility. Kim et al (1998) and Haussmann et al (2000) also suggested that this might be possible.…”
Section: Discussionmentioning
confidence: 99%